Properties and application of carbon composite brick for blast furnace hearth - Jiao K.X.; Zhang J.L.; Liu Z.J.; Zhao Y.G.; Hou X.M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A type of carbon composite brick was produced via the microporous technique using natural flack graphite, α-Al2O3 and high-quality bauxite chamotte (Al2O3≥87 mass%) as raw materials with fine silicon powder as additive. The composition and microstructure of the obtained carbon composite were characterized using chemical analysis, XRD and SEM with EDS. The high temperature properties of thermal conductivity, oxidization and corrosion by molten slag and hot metal of the composite were analyzed. Based on these, the type of carbon composite brick worked in a blast furnace hearth for six years was further sampled at different positions. The protective layer was found and its chemical composition and microscopic morphology were investigated. It is found that the carbon composite brick combines the good properties of both the conventional carbon block and ceramic cup refractory. The protective layer near the hot face consists of two separated sublayers, i.e. the slag layer and the carbon layer. A certain amount of slag phase is contained in the carbon layer, which is caused by the reaction of coke ash with the refractory. No obvious change in the chemical composition of the protective layer along the depth of the sidewall is found. This work provides a useful guidance for the extension of the lifetime of blast furnace hearths.